The Acute Red Eye - Megan Boysen Osborn; Christopher Gilani; Allen Yang; Marc Yonkers (eScholarship Publishing, University of California, 2016)
Audience: This modified team-based learning (mTBL) exercise is appropriate for junior or senior emergency medicine learners. Introduction: The acute red eye is a common chief complaint in the emergency department. It is essential that the emergency physician be knowledgeable about the differential diagnosis for the acute red eye and be able to distinguish between benign and sinister causes of the acute red eye. Objectives: By the end of this educational session, the learner will: 1) list 10 major causes for an acute red eye; 2) describe historical features that help distinguish between benign and serious causes of the acute red eye; 3) describe physical examination features that help distinguish between benign and serious causes of the acute red eye; and 4) use historical and physical examination features to distinguish between the 10 different causes of the acute red eye. Method: This is an mTBL session.